The Effect Of Information Technology on Employee Performance in Universities During The New Normal Era Of Covid-19 - Sulistyawati, Upik Sri; Bahruni, Bahruni (International Journal of Social Science and Business, 2021)
Covid has had an impact on the lives of employees generally including university employees. Social restrictions have posed a serious problem with regard to employee performance. In order to maximize employee performance, it is necessary to use information technology in the new normal life. The purpose of this study was to find out the effect of the use of information technology (X) on employee performance (Y). The subject of the research was employees of Sabang College of Economics in Banda Aceh and the Indonesian College of Informatics management in Banda Aceh. The type of the research used was explanatory research with a quantitative approach. The samples were 46 respondents at Sabang College of Economics in Banda Aceh and Indonesian College of Informatics management in Banda Aceh. The data analyses are descriptive analysis, inferential analysis, and multiple linear regression. The sampling technique used is saturation sampling. The results concluded that the independent variables have a significant influence on employee performance simultaneously and partially. Thus, of the two independent variables, efficacy has the most dominant influence on employee performance. The use of IT has the largest beta coefficient and t count. The results of multiple linear regression concluded that the independent variable has a significant influence on the dependent variable, namely employee performance, which is 64.7%. The remaining 35.3% is another variable that can affect employee performance. Other variables that can influence employee performance include employee motivation and ability. Information Technology has had some bearing on employee performance in universities during this the new normal life of Covid-19 period.Â